1990
DOI: 10.21273/hortsci.25.9.1164e
|View full text |Cite
|
Sign up to set email alerts
|

Variation for Genetic Recombination Among Tomato Plants Regenerated From Three Tissue Culture Systems

Abstract: Genetic recombination rates of hybrid plants regenerated from three tissue culture. systems were compared by backcrossing regenerated plants with mutant parents and comparing the observed crossover frequencies with those expected based on control plants raised from seed. Increased recombination rates and map distances were observed among plants from micropropagated shoot tips (4.5%-5.9%), cotyledon calli (3.7%-8.5%), and thin cell layers (2.8%-6.5%) between the sunny (sy) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
2
Order By: Relevance
“…The latter authors only observed 12 regenerated plants . We consider that it cannot be concluded from these reports that regeneration through a callus phase does not lead to any somaclonal variation in rose ; our results and those obtained on pea (Natali & Cavallini, 1987), tomato (Compton & Veilleux, 1991) and sugarcane (Irvine et al ., 1991) demonstrate the contrary .…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The latter authors only observed 12 regenerated plants . We consider that it cannot be concluded from these reports that regeneration through a callus phase does not lead to any somaclonal variation in rose ; our results and those obtained on pea (Natali & Cavallini, 1987), tomato (Compton & Veilleux, 1991) and sugarcane (Irvine et al ., 1991) demonstrate the contrary .…”
Section: Discussioncontrasting
confidence: 89%
“…The observed differences in frequency of callus development according to the floral parts used or to the development stages of zygotic embryos and floral parts confirm the importance, in a regeneration program, of the donor tissue (Evans, 1989 ;Compton & Veilleux, 1991), and its age (Burger et al ., 1990) . Using zygotic embryos, Burger et al .…”
Section: Discussionmentioning
confidence: 54%
“…Regenerants of C. maxima were also largely diploid (Lee et al, 2003), and only a single tetraploid plant regenerated on high cytokinin medium (1/207 regenerants in Lee et al (2003); 0.24% overall in Cucurbita, taking together our results and Lee et al, (2003)). However, a high rate of tetraploid regenerants, 30-45%, was noted in Cucumis (Ezura et al, 1992;Guis et al, 2000;Ç u¨ru¨k et al, 2003); much tetraploid regeneration has also been observed in tomato (Compton and Veilleux, 1991) and Arabidopsis (Morris and Altmann, 1994). Therefore, it is curious why Cucurbita species produce chimeric plants infrequently, but under genetic control.…”
Section: Production Of Chimeric Regenerantsmentioning
confidence: 99%
“…(Cardi et al ., 1992 ;Fleming et al ., 1992), and tomato, Lycopersicon esculentum Mill . (Compton & Veilleux, 1991 ;Jacobs & Yoder, 1989) . Ploidy of regenerated plants has been determined by performing somatic chromosome counts (Karp et al ., 1982), but can be more easily estimated by counting the number of chloroplasts per guard cell pair of leaf epidermal cells .…”
Section: Introductionmentioning
confidence: 99%
“…Ploidy of regenerated plants has been determined by performing somatic chromosome counts (Karp et al ., 1982), but can be more easily estimated by counting the number of chloroplasts per guard cell pair of leaf epidermal cells . This technique has been used to differentiate between diploid and tetraploid regenerants of melon (Fassuliotis'& Nelson, 1992), potato, (Cardi et al, 1993) and tomato (Compton & Veilleux, 1991 ;Jacobs & Yoder, 1989), and to distinguish between diploid and tetraploid watermelon plants obtained following treatment of diploid seedlings with colchicine (McCuistion & Elmstrom, 1993) . The purpose of this study was to investigate whether adventitious shoot regeneration from cotyledons of diploid watermelon could be used to produce fertile, non-chimeric tetraploid plants for use in breeding triploid hybrids .…”
Section: Introductionmentioning
confidence: 99%